Right to Self-Defence against Non-State Actors in the Context of Fight against Terrorism (Pravica do samoobrambe zoper nedržavne akterje v luči boja proti terorizmu) - Tina Korošec; Maruša Tekavčič Veber (Zbornik Znanstvenih Razprav)
The use of force in self-defence against non-state actors in the territory of another state not having effective control over activities of non-state actors is subject of numerous controversies. While the traditional approach limits the use of force in self-defence from Article 51 of the UN Charter to the inter-state relations, the ever-present threat of international terrorism triggered new trends in expanding the notion of self-defence to private armed attacks. In the past, countries justified their use of force against non-state actors on the territory of another state by attributing the attack to the host state. However, in the last few years, especially in the context of fight against ISIL in Syria, an unwilling or unable host state doctrine received an unprecedented attention. The authors of the paper present prevailing legal arguments for the use of force against non-state actors and assess whether a wider understanding of Article 51 of the UN Charter has emerged.